WHO REMAINS OFFLINE AND WHY? THE EVOLUTION OF INDIVIDUAL FACTORS INFLUENCING INTERNET NON-USE FROM 2011 TO 2019 IN A HIGHLY DIGITISED SOCIETY - Kappeler, Kiran; Festic, Noemi; Latzer, Michael (AoIR Selected Papers of Internet Research, 2020)
Switzerland is one of the countries with the highest internet penetration rates worldwide. Nevertheless, 600,000 people or 8% of the population remain offline. Being digitally excluded is problematic as internet use yields many advantages in everyday life. Obtaining real-time traffic information, applying for jobs, buying things or being an informed citizen increasingly requires internet use. Offline alternatives are often inferior, more expensive or non-existent. In countries where internet adoption is almost universal, the disadvantages of not being online are likely to increase and become even more detrimental to life chances. The choice of appropriate public policies to bridge digital divides, i.e., gaps between internet users and non-users, requires the empirical assessment of internet non-use in highly digitised societies. Therefore, this article investigates how digital divides have evolved from 2011 to 2019. Based on survey data representative of the Swiss population, binary logistic regressions show that structural inequalities significantly influence digital divides: lower income and educational level consistently predicted internet non-use and the age gap between users and non-users increased. Gender did not significantly affect non-use. The main self-reported reason for not using the internet was a perceived lack of usefulness. Proxy internet use, i.e., asking someone to do something online, significantly correlated with an increased intention to use the internet. Thus, an increased interest in the internet as well as indirect exposure to it are key enabling factors for internet use. These representative, long-term results form an input for more evidence-based public policies to mitigate the risks of digital exclusion.